Burmeistera andakiana and B. boyacensis (Campanulaceae, Lobelioideae), two new species from the Eastern Cordillera of Colombia - González, Favio; Garzón-Venegas, Javier (Phytotaxa, 2020)
Burmeistera andakiana and B. boyacensis are described as new species primarily from the Eastern Cordillera of Colombia. The first species, closely related to B. brachyandra and B. ramosa, grows in sub-Andean forests at the eastern slopes of the Cordillera in the departments of Caquetá and Putumayo, with a few lowland populations, being the only Colombian species of the genus that reaches Amazonian forests. The second species, closely related to B. orientalis, has been collected at edges of Andean forests in both flanks of the Eastern Cordillera in the department of Boyacá. The new species are illustrated and their relationships are discussed. Both species differ from their relatives by a number of vegetative and reproductive traits related to the indumentum of the stem, the architecture and size of leaves, the morphology and indumentum of floral organs, and the shape of the fruits. We suggest that both species be considered as critically endangered.